Peer-Mediated Interventions for Children with Intellectual and Developmental Disabilities: A Systematic Literature Review - M. Zulhadi; Damri Damri; Nurhastuti Nurhastuti; Rahmahtrisilvia Rahmahtrisilvia; M. Zulhadi; Damri Damri; Nurhastuti Nurhastuti (Universitas Negeri Malang, 2026)
Children with intellectual and developmental disabilities (IDD) frequently experience difficulties in social interaction and communication, highlighting the need for effective inclusive intervention strategies in educational settings. This study aims to systematically review the implementation and effectiveness of peer-mediated interventions for children with IDD in inclusive school contexts. A systematic literature review was conducted following the PRISMA 2020 guidelines, complemented by a bibliometric analysis using the Bibliometrix package. A total of 194 articles were identified, of which 13 studies met all inclusion criteria and were included in the final synthesis. The results indicate that peer-mediated interventions, such as peer tutoring, peer modeling, and peer support, significantly improve social interaction, communication skills, and behavioral engagement among children with IDD. The effectiveness of these interventions is influenced by key factors, including structured peer training, active teacher facilitation, and supportive learning environments. Additionally, the bibliometric findings reveal a growing research interest in this field, with dominant themes centered on social interaction, communication, and inclusive education. In conclusion, peer-mediated interventions represent an effective and practical approach to enhancing social and communicative outcomes while promoting inclusive learning environments for children with IDD. The findings suggest that educators should integrate structured peer-mediated strategies into classroom practices, while policymakers and researchers are encouraged to further develop and expand evidence-based inclusive interventions across diverse educational contexts.